The impact of conventions on hotel demand: Evidence from Indianapolis using daily hotel occupancy data - Colin Steitz; Joshua C. Hall (Journal of Risk and Financial Management, 2020)
This paper uses daily hotel occupancy data for the Indianapolis metro area from STR to estimate the effect of multi-day conventions on hotel demand. In addition to multi-day conventions, we hand collect data on other major events such as the Indy 500 and major sporting events. Hotel demand is an important part of the economic activity generated by multi-day events because hotel rooms are largely occupied by out-of-town guests and represent new local economic activity. We look at the effect of conventions and other large events in Indianapolis on average daily room rates, revenue per room, demand, occupancy, and total revenue. We find large and statistically significant effects for multi-day conventions on hotel demand with very little evidence of crowding out. A single day of a multi-day convention brings in approximately 928,000 in additional hotel revenue. Our findings contribute to the literature on the economic impact of large events such as conventions and sporting events that attract out-of-town visitors.
Keywords: R58; Z20; Z32; 330; conventions; football; hotel demand; sports economics; tourism; vistors